Confabulation views from neuroscience, psychiatry, psychology and philosophy - Hirstein, William (Oxford : Oxford University Press, 2009)
When people confabulate, they make an ill-grounded claim that they honestly believe is true, for example recalling an event from their childhood that never actually happened. This interdisciplinary book brings together some of the leading thinkers on confabulation in neuroscience, psychiatry psychology, & philosophy.
Description based on print version record.
Keywords: False memory syndrome; Self-deception.; Mythomania